A Frameshift Mutation in the Human Fibrinogen Aα-chain Gene (Aα [499] Ala Frameshift Stop) Leading to Dysfibrinogen San Giovanni Rotondo - Margaglione, Maurizio; Vecchione, Gennaro; Santacroce, Rosa; D’Angelo, Francesca; Casetta, Bruno; Papa, Maria Luisa; Grandone, Elvira; Minno, Giovanni Di (Thrombosis and Haemostasis, 2001)
We have investigated a 53-yr-old asymptomatic white man with decreased functional, but not immunologic, fibrinogen plasma levels together with prolonged thrombin and reptilase times, detected through routine coagulation studies prior to a surgical procedure. A new heterozygous single nucleotide deletion (C) at position Ala499 within the Aα-chain gene was identified, which predicted changes of the corresponding aminoacids encoded by the subsequent portion of the exon V and the appearance of a premature stop codon at position 518 (A [499]Ala frameshift stop). The new dysfunctional fibrinogen, San Giovanni Rotondo variant, was confirmed in vivo by SDS-PAGE analysis of HPLC-purified fibrinogen chains. Mass spectrum examination of the abnormal HPLC-purified peak gave an estimated mass (56,088 Da) similar to that predicted by DNA analysis of the mutated Aα-chain gene (56,088 Da) and, after tryptic digestion, the truncated Aα-chain was shown only in the propositus, who also carried normal Aα-chain. In addition, mass spectrum analysis of the tryptic digest of the abnormal chain confirmed the presence of a new and unpaired cysteine at the last position that was predicted to form a disulfide bridge with human serum albumin. Immuno-blot analysis confirmed that fibrinogen San Giovanni Rotondo variant, but not normal fibrinogen, contained substantial amounts of albumin. Present findings confirm that truncated Aα-chain lacking part of the terminal domain may be incorporated into mature fibrinogen molecules and normally secreted in the bloodstream.
Keywords: Dysfibrinogenemia; fibrinogen genes; mass spectrometry; truncated protein